HIGH DOSES OF IVERMECTIN CAUSE TOXIC EFFECTS AFTER SHORTTERM ORAL ADMINISTRATION IN RATS - Marjanović, Vladimir; Medić, Dragana; Marjanović, Djordje; Andrić, Nenad; Petrović, Miloš; Francuski Andrić, Jelena; Radaković, Milena; Marinković, Darko; Krstić, Vanja; Trailović, Saša (Slovenian Veterinary Research, 2024)
The anthelmintic macrocyclic lactones (MLs) are the most important endectocides in modern pharmacotherapy of parasitic infections. However, during the COVID 19 pandemic, ivermectin was used in humans against infection with the SARS-CoV-2 virus in doses significantly higher than the approved antiparasitic doses. This kind of application was created solely on the basis of in vitro tests, and is not officially approved in any country in the world. Therefore, we conducted a study on rats treated orally with 0.6, 1.2, 2.4 and 4.8 mg/kg of ivermectin for 5 days. Based on our investigation, ivermectin at the doses used in humans against the SARS-Co-2 virus (3, 6, 12 and 24 times higher than the antiparasitic dose 0.2mg/kg), causes changes in red blood cell counts and increases the levels of liver enzymes without visible clinical symptoms. Histopathological changes were recorded in the liver, kidneys and testicles of rats, and the highest dose tested led to bleeding in the brain tissue. Obviously, ivermectin somewhat increases concentration of the enzyme P-450 isoform 3A4, whose substrate it is, but the highest tested dose reduces its concentration in plasma to the control level. Notably, the concentrations of ivermectin recorded in plasma of treated rats, indicate that even high doses do not reach the in vitro IC50 value of ivermectin for SARS-CoV-2 reported in the literature. On the other hand, the concentrations of ivermectin in the brain approach the values that can manifest extremely toxic effects described in humans. Veliki odmerki ivermektina povzročajo toksične učinke pri podganah po kratkotrajnem peroralnem dajanju Izvleček: Protiglivični makrociklični laktoni (ML) so najpomembnejše učinkovine v sodobni farmakoterapiji parazitskih okužb. Vendar so med pandemijo covida-19 pri ljudeh proti okužbi z virusom SARS-CoV-2 uporabljali bistveno višje odmerke ivermektina od odobrenih antiparazitičnih odmerkov. Takšna uporaba je bila ustvarjena izključno na podlagi testov in vitro, vendar ni bila uradno odobrena v nobeni državi na svetu. Zato smo izvedli študijo na podganah, ki smo jih 5 dni peroralno zdravili z 0,6, 1,2, 2,4 in 4,8 mg ivermektina na kg telesne teže. Naša preiskava je pokazala, da ivermektin v povišanih odmerkih, ki se uporabljajo pri ljudeh proti virusu SARS-CoV-2 (3-, 6-, 12- in 24-krat večjih od antiparazitskega odmerka 0,2 mg/kg), povzroča spremembe v številu eritrocitov in zvišuje raven jetrnih encimov brez vidnih kliničnih simptomov. Histopatološke spremembe smo zabeležili v jetrih, ledvicah in testisih podgan, največji testirani odmerek pa je povzročil krvavitev v možganskem tkivu. Znano je, da ivermektin kot substrat nekoliko poveča koncentracijo encima P-450 izoforma 3A4, vendar največji testirani odmerek zmanjša njegovo koncentracijo v plazmi na kontrolno raven. Koncentracije ivermektina, zabeležene v plazmi zdravljenih podgan, kažejo, da tudi visoki odmerki ne dosežejo in vitro vrednosti IC50 ivermektina za SARS-CoV2, ki je navedena v literaturi. Po drugi strani pa se koncentracije ivermektina v možganih približujejo vrednostim, ki lahko povzročijo izjemno toksične učinke, opisane pri ljudeh. Ključne besede: ivermektin; toksičnost; SARS-CoV-2; citokrom P-450; P-gp; histopatološke spremembe; podgane